Аналіз можливостей кореляційного методу визначення джерела акустичної вибухової хвилі - Баженов, Віктор Григорович; Шиндерук, Тарас Дмитрович (НТУ "ХПІ", 2017)
Метою роботи є модельна оцінка можливостей кореляційного методу визначення джерела акустичної вибухової хвилі. Моделювання проводилося в програмному середовищі Matlab. В якості тестового зразка був обраний аудіозапис пострілу з пістолета Beretta M9. Аудіозапис був зашумлений "білим" (гаусовим) шумом. Була створена копія аудіозапису, зміщена у часі, щоб імітувати запізнення. Далі для обох сигналів була розрахована взаємна кореляційна функція, на основі якої визначалася затримка у часі між ними.

Model assessment of possibilities of correlation method to identifying the acoustic blast source is the main aim of this research. Modeling has been carried out in Matlab software environment. Shot record from a Beretta pistol has been chosen (from online sounds base www.freesound.org) as a test sample for analysis. Audio sampling frequency - 44 kHz, duration – 0.7 s, the number of bits per sample - 16. Signal to noise ratio was very high in the audio test. As a result of the experiment a "white" noise has been added to our audio signal to determine the potential correlation method. Shifted in time copy of this audio has been used for correlation analysis. Then mutual correlation function was calculated for both audio records, based on this calculation the time delay between these records has been determined. Correlation analysis showed that the delay limits could be precisely defined up to 14 dB, i.e. when the noise exceeds the signal 4 times more. It was also calculated the standard deviation for different signal to noise ratios of explored audio.
Analysis of possibilities of correlation method for determining the source of acoustic blast
Keywords: взаємна кореляційна функція; акустична хвиля; аудіозапис пострілу; "білий" шум; Matlab; mutual correlation function; acoustic wave; shot record